Virulence Plasmids of Rhodococcus equi Isolates From Cuban Patients With AIDS - Salazar-Rodríguez, Daniel; Aleaga-Santiesteban, Yamilé; Iglesias, Enrique; Plascencia-Hernández, Arturo; Pérez-Gómez, Héctor R.; Calderón, Enrique J.; Vázquez-Boland, José A.; de Armas, Yaxsier (Frontiers in Veterinary Science, 2021)
Rhodococcus equi infection is considered a zoonosis and an opportunistic bacterium capable of infecting immunosuppressed patients, mainly people living with HIV/AIDS. The pathogenicity of R. equi is associated with a plasmid that encodes for a family of ‘‘Virulence Associated Proteins'' (VAPs). Unfortunately, molecular typing of R. equi is insufficiently developed. Little is known about the epidemiology and transmission of this pathogen among multiple hosts. We report a case series study of 26 R. equi isolates of the same number of people living with HIV/AIDS conducted during the period between January 2010 and December 2016 at Institute of Tropical Medicine "PedroKourí". We used pre-existing TRAVAP typing system based on traA, pVAPA and pVAPB markers for classifying R. equi strains into four categories. Molecular analysis using the PCR technique showed that 4 out of 26 isolates (15.4%) were positive for the pVAPA plasmid. The overall prevalence of pVAPB carriage (vapB gene) in the sample was 23.1% (6/26). The traA gene was positively identified in 11 (42.3%) cases. Finally, only one isolate of R. equi carried the pVAPN plasmid. In this study, the TRAVAP negative isolates achieved the highest frequency (53.8%) in the whole sample. To our knowledge, this work is the first report of molecular characterization of R. equi isolates in Cuban people living with HIV/AIDS. Our findings show the impact of this pathogen on immunosuppressed patients, zoonotic power (frequent contact with pigs and pork meat), and raise the question about a potential threat to public health due to R. equi infection.